Organochlorine, organophosphate, synthetic pyrethroids assessment in bovine milk and water samples of Jaipur, Rajasthan. - SHARMA, S; SHARMA, V; JAIN, J; AGARWAL, S; DAHIYA, D K; KHAN, A (The Indian Journal of Animal Sciences, 2016)
Important pesticides (organo- chlorine, -phosphate, and synthetic pyrethroids) in bovine milk samples, water and fodder collected from the eight different blocks of Jaipur, Rajasthan were monitored in the present study. Simultaneously, a survey was conducted regarding the usage of pesticides in these areas in particularly on animal feed. Sixty four samples each of wheat (Triticum) straw and bajra (Pennisetum glaucum) stover, 32 samples each of lucerne (Medicago sativa), water, indigenous cow milk, 64 samples each of exotic cow and buffalo milk were analysed. Gas chromatography results revealed that pesticides in milk, water and fodder samples were absent. The attributed reason being the low consumption and prevailing environmental conditions, viz. soil type, surface water depth, intensity and length of sunlight exposure, temperature etc. which leads to the faster degradation of these pesticides.